M1 RNA is important for the in-cell solubility of its cognate C5 protein: Implications for RNA-mediated protein folding - Son, Ahyun (RNA Biol, 2015)
It is one of the fundamental questions in biology how proteins efficiently fold into their native conformations despite off-pathway events such as misfolding and aggregation in living cells. Although molecular chaperones have been known to assist the de novo folding of certain types of proteins, the role of a binding partner (or a ligand) in the folding and in-cell solubility of its interacting protein still remains poorly defined. RNase P is responsible for the maturation of tRNAs as adaptor molecules of amino acids in ribosomal protein synthesis. The RNase P from Escherichia coli, composed of M1 RNA and C5 protein, is a prototypical ribozyme in which the RNA subunit contains the catalytic activity. Using E. coli RNase P, we demonstrate that M1 RNA plays a pivotal role in the in-cell solubility of C5 protein both in vitro and in vivo. Mutations in either the C5 protein or M1 RNA that affect their interactions significantly abolished the folding of C5 protein. Moreover, we find that M1 RNA provides quality insurance of interacting C5 protein, either by promoting the degradation of C5 mutants in the presence of functional proteolytic machinery, or by abolishing their solubility if the machinery is non-functional. Our results describe a crucial role of M1 RNA in the folding, in-cell solubility, and, consequently, the proteostasis of the client C5 protein, giving new insight into the biological role of RNAs as chaperones and mediators that ensure the quality of interacting proteins.